A convenient route to symmetrically and unsymmetrically substituted 3,5-diaryl-2,4,6-trimethylpyridines via Suzuki–Miyaura cross-coupling reaction - Dariusz Błachut; Joanna Szawkało; Zbigniew Czarnocki (Beilstein Journal of Organic Chemistry, 2016)
A series of differently substituted 3,5-diaryl-2,4,6-trimethylpyridines were prepared and characterized using the Suzuki–Miyaura coupling reaction with accordingly selected bromo-derivatives and arylboronic acids. The reaction conditions were carefully optimized allowing high yield of isolated products and also the construction of unsymmetrically substituted diarylpyridines, difficult to access by other methods.